Solar UAV : airframe configuration and design - Kurniawan, Juan Septiano. (2013)
The growth of solar cells technology has made the development of solar-powered unmanned aerial vehicles (UAVs) possible. Here in Nanyang Technological University, a 3-year project is underway to develop a medium altitude, long endurance (MALE) solar-powered UAV with 24-hr endurance. The author was involved in the 2nd year of the project, aimed at building on the knowledge of the past year’s progress and preparing the subsequent group of students to manufacture the aircraft in 2014.